2020
DOI: 10.1038/s41467-020-19228-4
|View full text |Cite
|
Sign up to set email alerts
|

Local community assembly mechanisms shape soil bacterial β diversity patterns along a latitudinal gradient

Abstract: Biodiversity patterns across geographical gradients could result from regional species pool and local community assembly mechanisms. However, little has been done to separate the effects of local ecological mechanisms from variation in the regional species pools on bacterial diversity patterns. In this study, we compare assembly mechanisms of soil bacterial communities in 660 plots from 11 regions along a latitudinal gradient in eastern China with highly divergent species pools. Our results show that β diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 60 publications
5
56
0
Order By: Relevance
“…4), indicating habitat heterogeneity also influenced microbial community patterns. The effects of habitat heterogeneity on microbial communities can be observed in two aspects: the regional species pool and species abundance distribution (Myers et al ., 2015; Zhang et al ., 2020). Huge differences in the local species pool between the LH and YLJ coastal areas were shown in the present study, as the shared ratio of bacteria and protists only accounted for 7.2% and 14.1% respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), indicating habitat heterogeneity also influenced microbial community patterns. The effects of habitat heterogeneity on microbial communities can be observed in two aspects: the regional species pool and species abundance distribution (Myers et al ., 2015; Zhang et al ., 2020). Huge differences in the local species pool between the LH and YLJ coastal areas were shown in the present study, as the shared ratio of bacteria and protists only accounted for 7.2% and 14.1% respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effects of local community assembly mechanisms, a novel index, β‐deviation, has been recently explored, which can recognize the dominant ecological processes shaping the β‐diversity pattern of microbial communities under the control of the regional species pool (Zhang et al ., 2020). The fraction of pairwise comparisons with β‐deviation <0 represented homogeneous selection or homogenizing dispersal as the dominant mechanism for local community assembly, whereas those with β‐deviation >0 were considered heterogeneous selection or dispersal limitation.…”
Section: Methodsmentioning
confidence: 99%
“…The diversity and composition of biotic communities could be shaped by regional species pools or local abiotic (e.g. soil properties) and biotic heterogeneity (Buckley et al ., 2003; Tedersoo et al ., 2014; Horvitz et al ., 2017; Zhang et al ., 2020). In this study, species pool and richness CV explained a proportion of variance in the diversity and composition of plants and arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…The dissimilarity in root‐associated fungi among plants could be affected by both regional (such as the size of species pools, termed γ diversity) and local (such as heterogeneity in abiotic and biotic factors) processes (Zhang, Liu, et al, 2020). In this study, we found a positive relation between regional OTU richness and overall fungal dissimilarity only when the native and invasive plants were treated as separate groups.…”
Section: Discussionmentioning
confidence: 99%